A COMPARATIVE STUDY BETWEEN MULTIPLE CHOICE AND SHORT ANSWER TEST TOWARDS STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Ervi Kamaruddin; H.Bahrun Amin; Junaid (Journal of Language Testing and Assessment, 2022)
This research was about a multiple choice comparative study and short answer on students' reading comprehension achievement in the ninth grade of SMPN 2 Ulaweng. The problem statement of this research was there a significant difference of the students' achievement in reading comprehension by using multiple choice test and their achievement on the short answer test?. The purpose of this research was to find out a significant difference of the students‟ achievement in reading comprehension by using multiple choice test and their achievement on he short answer test as the measure of reading comprehension.This study applied a quantitative design, with a sample of 40 students divided into 2 classes. The instrument used was in the form of a test which is divided into two types of multiple choice and short answer.The results of this study indicate that the students‟ achievement in multiple choice test, higher than students‟ achievement in the short answer test. The analysis of the mean score gap between the closed test and multiple choice in the test was different. The mean score of the multiple choice was 71.5 and 47.5 short answer. From the result the researcher concluded that multiple choice test is better than short answer test to increase students‟ achievement in reading comprehension at the ninth grade students of SMP Negeri 2 Ulaweng.